Automated temperature and sanitization measurement totem with Arduino in Tinkercad (Research, Society and Development, 2023)
The 2019 Global Pandemic has plagued the world due to the high degree of contamination and the risk of death for people with physiological condition. One of the symptoms of this infection is the presence of fever, and during the peak of the disease, measurements of temperatures were performed with laser thermometers by employees at a small distance from the citizen. Although hand hygiene has always been important, it has become crucial during the pandemic to adopt rigorous effective hand hygiene practices to contain the spread of the virus. The simple act of hand hygiene not only prevents them from becoming disease-carrying vehicles, but is also crucial in places where pathogens are common, such as hospitals. In this scenario, an experimental research was conducted, based on the computer model developed, it became possible to create an autonomous totem capable of droping hand sanitizer into the user' hand and measuring body temperature without direct human touch. This concept was designed through Tinkercad simulation platform, which offers the simulation of electronic circuits and their use in a similar way to physical form. The implementation of the totem proved to be feasible, allowing the start of the parameters metioned above with no need of users physical contact and highlighting the feasibility of automation to enhance the combat against COVID-19.